2020
DOI: 10.1101/2020.03.11.986935
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Binding dynamics of alpha-actinin-4 in dependence of actin cortex tension

Abstract: Mechano-sensation of cells is an important prerequisite for cellular function, e.g. in the context of cell migration, tissue organisation and morphogenesis. An important mechano-chemical-transducer is the actin cytoskeleton. In fact, previous studies have shown that actin cross-linkers, such as α-actinin-4, exhibit mechanosensitive properties in its binding dynamics to actin polymers. However, to date, a quantitative analysis of tension-dependent binding dynamics in live cells is lacking. Here, we present a ne… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…Additionally, previous research has indicated that α-actinin 4 acts as a mechanosensitive actinbinding protein through its catch-slip activity which allows it to bind or release actin based on mechanical tension. This could potentially explain why we observe α-actinin 4 is more important for the dynamic actin remodeling in membrane ruffles (Xu et al, 1998;Fukumoto et al, 2015;Hosseini et al, 2020). In addition, while we were interested in trafficking of macropinosomes to the lysosome as that provides nutrients to the proliferating tumor cells, the actinin proteins may also regulate recycling of material from macropinosomes back to the plasma membrane via interactions with other actin nucleating machinery such as WASH.…”
Section: Discussionmentioning
confidence: 97%
“…Additionally, previous research has indicated that α-actinin 4 acts as a mechanosensitive actinbinding protein through its catch-slip activity which allows it to bind or release actin based on mechanical tension. This could potentially explain why we observe α-actinin 4 is more important for the dynamic actin remodeling in membrane ruffles (Xu et al, 1998;Fukumoto et al, 2015;Hosseini et al, 2020). In addition, while we were interested in trafficking of macropinosomes to the lysosome as that provides nutrients to the proliferating tumor cells, the actinin proteins may also regulate recycling of material from macropinosomes back to the plasma membrane via interactions with other actin nucleating machinery such as WASH.…”
Section: Discussionmentioning
confidence: 97%
“…Motivated by experimental observations, see e.g. [21][22][23][24] , we anticipate that the unbinding rate of molecular regulators of active stress depends on the local trace of the in-plane stress t i i . In particular, we make the choice of a Bell model dependence…”
Section: Constitutive Equations For An Active Gel On a Curved Surface...mentioning
confidence: 99%
“…Some actin cross-linkers such as α-actinin-4 and myosin have been shown to exhibit a catch-bond behavior 21,23,37 .…”
Section: B Two Molecular Regulator Species With Opposite Mechanosensi...mentioning
confidence: 99%
See 2 more Smart Citations